1993
DOI: 10.1159/000263823
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Terbutaline and Betamethasone on Glucose Homeostasis in Preterm Labor

Abstract: The short- and long-term effects of simultaneous administration of terbutaline and betamethasone were investigated in 8 gravidas treated for preterm labor. Their plasma concentrations of glucose, insulin, glucagon, C-peptide, lactate and potassium were compared to a control group receiving intravenous magnesium sulfate and betamethasone. The patients on terbutaline therapy had a marked hyperglycemia at 11 h which remained elevated for 48 h. There was a simultaneous rise in plasma insulin and C-peptide, and a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…Although many investigators have studied the effects of corticosteroids on glucose metabolism, 15 there are a limited number of studies investigating the effects of corticosteroids related to the diagnosis of gestational diabetes. Adam et al 16 found significant elevation in maternal hyperglycemia during the 11 to 48 hours period after combinated usage of oral terbutaline and betamethasone in 8 gravidas treated for preterm labor. However, only one of these eight cases had abnormal GTT at 1 week of therapy and this suggest that glucocorticoids potentiate the hyperglycemic response of terbutaline and this effect seems to be temporary.…”
Section: Discussionmentioning
confidence: 99%
“…Although many investigators have studied the effects of corticosteroids on glucose metabolism, 15 there are a limited number of studies investigating the effects of corticosteroids related to the diagnosis of gestational diabetes. Adam et al 16 found significant elevation in maternal hyperglycemia during the 11 to 48 hours period after combinated usage of oral terbutaline and betamethasone in 8 gravidas treated for preterm labor. However, only one of these eight cases had abnormal GTT at 1 week of therapy and this suggest that glucocorticoids potentiate the hyperglycemic response of terbutaline and this effect seems to be temporary.…”
Section: Discussionmentioning
confidence: 99%
“…In der vorliegenden Arbeit zeigte sich eine mit anderen Studien [6,17] Einige Autoren fordern eine langfristige Nachbeobachtung der Kinder hinsichtlich ihrer psychomotorischen und neurologischen Entwicklung. Die Kürze der hyperglykämischen Intervalle lassen einen Einfluss allerdings unwahrscheinlich erscheinen.…”
Section: Zusammenfassung Und Diskussionunclassified